Destruction of Reinforced Concrete by Electric Impulse Discharges: Experiment and Simulation; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Yudin A. S. Artem Sergeevich; Kuznetsova N. S. Nataliya Sergeevna; Bakeev R. A.; Zhgun (Jgun) D. V. Dmitry Vladimirovich; Stefanov Yu. P. (2017, 2017)
Title screen